Influence of storage temperatures and storage time of dry leaves on patchouli [Pogostemon cablin (Blanco) Benth.] essential oil - Maria de Fatima Arrigoni-Blank; Priscilla Santana Santos; Arie Fitzgerald Blank; Fabiany de Andrade Brito; Thiago Matos Andrade; Daniela Aparecida de Castro Nizio; Péricles Barreto Alves (Bioscience Journal, 2020)
Patchouli [Pogostemon cablin (Blanco) Benth.] is a plant of the family Lamiaceae, widely used as an essential oil in the cosmetics and perfumery industry. This study aimed to evaluate the influence of storage time and temperature of dry leaves on the patchouli essential oil content and chemical composition. The experiment was performed in a completely randomized design in a 6x2x2 factorial scheme, testing storage time (0, 1, 2, 4, 8, and 16 weeks) and temperature (28°C and 33°C) of dry leaves of two patchouli genotypes (POG-015 and POG-021).  The variables essential oil content and chemical composition, and the identification of fungus during storage were evaluated. Results showed that the storage significantly influenced the essential oil content. Patchoulol was identified as the major compound in both genotypes, ranging from 55.05% to 68.77% (POG-15) and from 52.83% to 64.06% (POG-021). Based on the results of patchoulol, dry leaves of both genotypes (POG-015 and POG-021) can be stored for up to eight weeks at 28- 33°C without altering the essential oil quality.